Conjugate aurora observations by the Gjøa and Discovery expeditions - Egeland, Alv (Hist. Geo Space. Sci., 2024)
From 1901 to 1912 – known as the “heroic period” of Arctic and Antarctic exploration – great inroads were made (not only geographic but also scientific) to our knowledge of the continent. At Amundsen's Expedition through the Northwest Passage, measurements of the geomagnetic field and visual auroras were carried out for 19 months at Gjoa Haven (Gjøahavn in Norwegian; geographic coordinates 68°37′10′′ N, 95°53′25′′ W). Scott's Discovery Expedition – at Cape Armitage, McMurdo (coordinates 77.86° S, 166.69° E), Antarctica – carried out the same type of measurements. Their observations were carried out geomagnetically conjugate to Gjoa Haven, with both stations close to 78° magnetic latitude. In addition, measurements were overlapping in time during 1903–1904. However, these two stations are located at different longitudes, so there is a difference in local time between the stations of about 6.5 h. Gjoa Haven and Cape Armitage are conveniently located for separating disturbances in the polar cap regions caused by solar electromagnetic radiations or the solar wind. Auroras were observed during 7 months per year. This gave a unique possibility to compare conjugate characteristics of polar cap auroras. Comparing conjugate geophysical data introduces some difficulties. During the winter season at Gjoa Haven, they had a bright summer in Antarctica, and visa versa. Thus, simultaneous temporal and spatial ionospheric variations can be marked differently. Still, the average diurnal and seasonal variations were similar. The quantity of the auroral data from Cape Armitage was larger because there they had a continuous watch of the sky. The main findings regarding polar cap auroras are the following. Three different auroral forms dominate the polar cap. Low-intensity auroral bands – then called streamers – were the dominating auroral forms morning and afternoon. The number of auroral events in 1903 was nearly twice that in 1902 and 1904. A marked midwinter maximum was observed at both stations. Many displays were observed poleward of the oval. The large fraction was associated with weak magnetic disturbances. Some forms of polar cap aurora have special magnetic signatures and seem to be anti-correlated with Kp. They can be mapped even if they are not seen. According to recent satellite measurements (Newell et al., 2009), they are probably caused by polar rain and/or photoelectrons.
Keywords: Antarktis; Discoveryekspedisjonen; fysikk; polarfarere; polarområdene; romfysikk; sørlys

Norway and the Antarctic - Stephenson, Robert B; [Barr, Susan] (The Erebus and Terror Press, 2017)
Keywords: Antarktis; Nordmenn; norske ekspedisjoner; polarfarere

Ekspedisjoner og begivenheter - Barr, Susan (Norsk polarhistorie, 2004)
Keywords: Antarktis; Nordmenn; Norge; ekspedisjoner; oppdagelsesreiser; polarfarere

Polarheltene - minner og monumenter - Eriksen, Anne (Norsk polarhistorie, 2004)
Keywords: Antarktis; Nordmenn; Norge; ekspedisjoner; polarfarere; polarområdene

James Cook - Haffner, Einar (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1928)
Det er i år 150 år siden James Cook døde. Der er så mange jubileer og minnefester i våre dager at man undertiden synes det kan bli litt for meget av det gode. Men de efterfølgende minneord er helliget en mann som ingen der er geografisk interessert, nogensinde bør glemme.
Keywords: James Cook; Sørishavet; geografi; oppdagelsesreiser; polarekspedisjoner; polarfarere